Predatory activity of Macrolophus caliginosus Wagner (Heteroptera: Miridae) on Cacyreus marshalli Butler (Lepidoptera: Lycaenidae) and its assessment using a specific marker (Bollettino di zoologia agraria e bachicoltura, 2024)
During 2006 a study was carried out to assess the predatory activity of the autochthonous mirid Macrolophus caliginosus Wagner on the butterfly Cacyreus marshalli Butler. This exotic phytophagous Lycaenid recently introduced to Europe, also known as Geranium Bronze, is a pest of cultivated Geranium. Two different experimental approaches were performed. The first one was carried out in greenhouse and concerned a comparison trial between geranium plants (Pelargonium x hortorum Bailey) infested by Geranium Bronze, "with" or "without" M. caliginosus input. The second one concerned the development of a specific C. marshalli molecularmarker, with the aim to demonstrate, by PCR, the predatory activity of M. caliginosus on the exotic Lycaenid. The molecular marker was designed on mithocondrial citocrome-oxidase subunit I gene sequence. The comparison trial confirmed the hypothesis that the mirid feeds on eggs and young larvae of Geranium Bronze: the Lycaenid infestation was strongly reduced in the treatment "with" M. caliginosus, in comparison with the treatment "without" it. These data were supported by molecular analysis, since DNA of C. marshalli was detected in the digestive system of M. caliginosus caught outdoors on infested geranium plants. Some PCR featuresand the possible employment of M. caliginosus as biocontrol agent of C. marshalli, are briefly discussed.
Keywords: Cacyreus marshalli; Macrolophus caliginosus; biological control; Geranium Bronze Butterfly; molecular marker; PCR (Polymerase Chain Reaction)